Structures Congress 2018 : bridges, transportation structures, and nonbuilding structures : selected papers from the Structures Congress 2018, April 19-21, 2018, Fort Worth, Texas - Soules, J. G. (J. Greg) (American Society of Civil Engineers, 2018)
This collection contains 49 peer-reviewed papers on bridges, transportation structures, and other nonbuilding structures presented at the Structures Congress 2018, held in Fort Worth, Texas, April 19-21, 2018.